2022
DOI: 10.1109/tim.2022.3153991
|View full text |Cite
|
Sign up to set email alerts
|

Improved Method for Permittivity Determination of Dielectric Samples by Free-Space Measurements

Abstract: A new deembedding technique is proposed for relative complex permittivity ε r determination of dielectric materials using gated free-space measurements. Its three main features are 1) it does not require any formal calibration procedure (calibration-free); 2) it is position-insensitive; and 3) it extracts ripple-free ε r due to gating process. The objective function derived to determine ε r by the proposed method is validated by free-space measurements of three dielectric samples (polypropylene, polyethylene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…4. Different from the free-space measurement setup based on an arching reflection method in the study [36], our measurement setup, similar to those in the studies [11], [15]- [18], [37], is useful for measuring both reflection and transmission properties of prepared SCGC samples with different NS and SF additives. It includes a vector network analyzer (VNA) instrument, two horn antennas, and two coaxial-line cables [37]- [39].…”
Section: B Measurement Procedures For Electromagnetic Testsmentioning
confidence: 99%
See 3 more Smart Citations
“…4. Different from the free-space measurement setup based on an arching reflection method in the study [36], our measurement setup, similar to those in the studies [11], [15]- [18], [37], is useful for measuring both reflection and transmission properties of prepared SCGC samples with different NS and SF additives. It includes a vector network analyzer (VNA) instrument, two horn antennas, and two coaxial-line cables [37]- [39].…”
Section: B Measurement Procedures For Electromagnetic Testsmentioning
confidence: 99%
“…Different from the free-space measurement setup based on an arching reflection method in the study [36], our measurement setup, similar to those in the studies [11], [15]- [18], [37], is useful for measuring both reflection and transmission properties of prepared SCGC samples with different NS and SF additives. It includes a vector network analyzer (VNA) instrument, two horn antennas, and two coaxial-line cables [37]- [39]. The VNA instrument (Keysight Instruments with model N9918A) Because we used the time-gating option of the VNA, to be discussed in Section IV-B, which was set around the sample region by selecting a proper time interval in the time-gating process [37] and because prepared samples had relatively larger transverse planes in square form (500 × 500 mm 2 ), it was observed that microwave absorbers positioned near the SCGC samples did not much improve our free-space measurements [38], [39].…”
Section: B Measurement Procedures For Electromagnetic Testsmentioning
confidence: 99%
See 2 more Smart Citations
“… 18 . These effects can also be removed by using spot-focusing antennas 15 17 which in turn limit the frequency band and increase overall budget of the measurement system especially for high-frequency measurements. Another issue related to free-space measurements is the effects of undesired signals from ground or between the antenna and the sample, which can overall affect the accuracy of the measurements.…”
Section: Introductionmentioning
confidence: 99%